The mortality crisis in transition economies - Giovanni Andrea Cornia (IZA World of Labor, 2016)
Large and sudden economic and political changes, even if potentially positive, often entail enormous social and health costs. Such transitory costs are generally underestimated or neglected by incumbent governments. The mortality crisis experienced by the former communist countries of Europe—which caused ten million excess deaths from 1990 to 2000—is a good example of how the transition from a low to a high socio-economic level can generate huge social costs if it is not actively, effectively, and equitably managed from a public policy perspective.
Keywords: I14; I18; D6; J64; P3; Z22; 330; transition; mortality; psychosocial stress; social policies; alcohol consumption; eastern Europe